2018
DOI: 10.2174/1871526516666161230123133
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Antibacterial and Wound Healing Activities of Roman Chamomile (Chamaemelum nobile)

Abstract: Our study indicated that antibacterial and wound healing activities of C. nobile ointment were notable. C. nobile therapy in combination with antibiotics can also be useful because medicinal plants contents operate in synergy with antibiotics. These results revealed the value of plant extracts to control antibiotic resistant bacteria in wound infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…During this process, re-epithelialization, fibroplasia, angiogenesis, and extracellular matrix production are important steps that are generally dependent on the immunological condition of the host [ 23 , 46 , 47 , 48 ]. The use of natural compounds represents an alternative to chemical compounds used to induce healing, and it showed satisfactory results [ 23 , 24 , 26 , 49 ]; the use of pomegranate extracts to accelerate the healing process was described [ 1 , 22 , 25 , 50 ]. Additionally, silver nanoparticles (AgNPs) have drawn attention due their versatile functions such as antimicrobial, anti-inflammatory, and antiangiogenetic properties, and wound healing promotion, and they are used as interesting tools to overcome emerging medical challenges [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this process, re-epithelialization, fibroplasia, angiogenesis, and extracellular matrix production are important steps that are generally dependent on the immunological condition of the host [ 23 , 46 , 47 , 48 ]. The use of natural compounds represents an alternative to chemical compounds used to induce healing, and it showed satisfactory results [ 23 , 24 , 26 , 49 ]; the use of pomegranate extracts to accelerate the healing process was described [ 1 , 22 , 25 , 50 ]. Additionally, silver nanoparticles (AgNPs) have drawn attention due their versatile functions such as antimicrobial, anti-inflammatory, and antiangiogenetic properties, and wound healing promotion, and they are used as interesting tools to overcome emerging medical challenges [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of natural extracts applied as antimicrobial drugs is a growing field in science that has demonstrated interesting and promising results [ 22 , 23 ]. Following this scenario, several plant extracts were studied for the treatment of wound healing, such as extracts from Chrozophora tinctoria , Hibiscus rosa-sinensis L., Pongamia pinnata , Persea americana , Chamaemelum nobile L., and Punica granatum [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has shown activity against both Gram-positive and Gram-negative bacteria. The antibacterial potential was studied by Kazemian et al [ 36 ]. Wounds were created by incision using a blade and subsequently infected with Pseudomonas aeruginosa strains.…”
Section: Biological Activities Of Chamomilementioning
confidence: 99%
“…The results showed that the C. nobile ointment significantly inhibited P. aeruginosa and also stimulated wound healing compared with the control. 115 2.6. E. cannabinum E. cannabinum, commonly known as hemp-agrimony, is a herbaceous plant common in Europe, North America, Central Asia, and Northern Africa.…”
Section: Nobilementioning
confidence: 99%